PENGARUH PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN PADA PT PENERBIT ERLANGGA MAHAMERU CABANG SUKABUMI - Supenti, Penti; Sobar, Agus; Rianto, Toha (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2023)
This kind of research uses a quantitative method and is descriptive. This study's goal is to learn more about how offering incentives to workers at the PT Publisher Erlangga Mahameru Sukabumi branch affects their performance. This study collected data from all 50 employees of PT Publisher Erlangga Mahameru Sukabumi branch. The procedures used in sampling are population census study techniques and questionnaire methods used to collect data to use the full population as a sample. It uses a simple linear regression analysis method. The results showed that the incentive provision of PT Publisher Erlangga Mahameru Sukabumi branch was good enough. It can be seen in the answers from questionnaires distributed by researchers, where many PT Publisher Erlangga Mahameru Sukabumi branch employees have expressed satisfaction. Employee performance is quite good from the influence generated by providing incentives and other rewards. The effect of providing incentives on employee performance at PT Publisher Erlangga Mahameru Sukabumi branch by 50% and 50% is influenced by other factors.